Boosting oxygen evolution reaction on graphene through engineering electronic structure. (December 2020) - Wang, Changlai; Tong, Huigang; Lu, Jian; Liu, Bin; Zheng, Fangcai; Tao, Weiwei; Zhang, Wenjun; Chen, Qianwang
Abstract: Graphene is electrochemically inert toward the oxygen evolution reaction (OER) owing to the zero-band property, nevertheless doping it with heteroatoms could modulate its electronic structure and increase its chemical reactivity. Notwithstanding the achieved progress, the overpotential of heteroatom doped graphene is still very large. Herein, we coat FeNiIr nanoalloys by nitrogen-doped graphene with core-shell structure (FeNiIr@NG) to further boost the OER activity on graphene surface. Because of the unique core-shell structure, FeNiIr@NG delivers high electrocatalytic OER activity and durability, even exceeding that of commercial IrO2 electrocatalyst. Density functional theory calculations demonstrate that the nanoalloys core could transfer electron to outer graphene shells, which optimizes the electronic structure of graphene and balances the adsorption strength of OER intermediates, thereby triggering OER activity on the graphene surface. Graphical abstract: The OER activity on graphene surface is triggered through coating FeNiIr nanoalloys to modulate the electronic structure of graphene. Image 1 Highlights: The OER activity on graphene surface is triggered by coating FeNiIr with graphene. This unique FeNiIr@NG core-shell catalyst exhibits better OER activity than IrO2 . The adsorption strength of ∗ O, ∗OH and ∗OOH is depended on electronic structure.